2020
DOI: 10.1007/s11356-020-08763-8
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater insects of different feeding guilds ingest microplastics in two Gulf of Guinea tributaries in Nigeria

Abstract: Plastic pollution has enormous impacts on freshwater and marine ecosystem health, and it is one of the topmost environmental concerns of the current geological period (i.e. the Anthropocene). Thus, the goal of our study was to provide baseline information and bridge the information gap on the occurrence of microplastics (MPs) in African freshwater systems, using two tributaries of the Gulf of Guinea (Ogun and Osun Rivers) in Nigeria as a case study and three freshwater insect species of different feeding guild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 28 publications
(42 reference statements)
5
45
0
Order By: Relevance
“…This is due to having negligible drawbacks for the damage of MP particles. Another report found that a combination of different chemicals; hydrogen peroxide with alkaline base (H 2 O 2 with KOH) were used for the oxidation of impurities (Akindele et al 2020 ), and the purification of MP particles from the matrix (Tata et al 2020 ) in different samples. A critical selection of the oxidizing agents is an important issue for the effective detection of all the MP particles and components that only degrades the organic matter without degrading plastics.…”
Section: Sampling Techniques Mps Preparations and Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is due to having negligible drawbacks for the damage of MP particles. Another report found that a combination of different chemicals; hydrogen peroxide with alkaline base (H 2 O 2 with KOH) were used for the oxidation of impurities (Akindele et al 2020 ), and the purification of MP particles from the matrix (Tata et al 2020 ) in different samples. A critical selection of the oxidizing agents is an important issue for the effective detection of all the MP particles and components that only degrades the organic matter without degrading plastics.…”
Section: Sampling Techniques Mps Preparations and Detection Methodsmentioning
confidence: 99%
“…However other infrequent shapes, such as pellets, irregular shapes, spheres are originated from different commercial goods and transportations, especially occurred in the municipality (Fred-Ahmadu et al 2020 ). The high percentage of filaments, fragments, and fibers particularly were recorded within fish (Adeogun et al 2020 ), larvae (Akindele et al 2020 ), and insect (Dahms et al 2020 ) samples. Spheres and sheet MP percentage abundant were observed in a small proportion as compared with other shapes.…”
Section: Physical and Structural Characteristics Of Microplastics In The African Water Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…MPs in water have been investigated in Lake Naivasha, Kenya [13] and in sediments in seven tributaries of the Bizerte Lagoon in Tunisia [14]. For Nigeria, one study about MP ingestion of gastropods in the river Osun, Nigeria (a tributary of the Lagos Lagoon), and another about MP ingestion of aquatic insect larvae has recently been published [15]. MPs in fish in the River Nile, Egypt [16], in pelagic and demersal fish [17] and two local fish species [18] in the marine waters of Ghana were also investigated.…”
Section: Introductionmentioning
confidence: 99%